Stakeholder democracy represented democracy in a time of fear - Dodds, Felix (Routledge, 2019)
In the context of sustainable development, this book describes how we are moving from representative to participatory democracy, and how we are now in a "stakeholder democracy," which is working to strengthen represented democracy in a time of fear.